2020
DOI: 10.1002/anie.202004264
|View full text |Cite
|
Sign up to set email alerts
|

Key Intermediate Species Reveal the Copper(II)‐Exchange Pathway in Biorelevant ATCUN/NTS Complexes

Abstract: The amino‐terminal copper and nickel/N‐terminal site (ATCUN/NTS) present in proteins and bioactive peptides exhibits high affinity towards Cu II ions and have been implicated in human copper physiology. Little is known, however, about the rate and exact mechanism of formation of such complexes. We used the stopped‐flow and microsecond freeze‐hyperquenching (MHQ) techniques supported by steady‐state spectroscopic and electrochemical data to demonstrate the formation of partially coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(101 citation statements)
references
References 38 publications
7
67
0
Order By: Relevance
“…The value found for Aβ 4–16 agrees fairly well with that recently determined by competition and double mixing stopped‐flow experiments and attributed to the formation of the Cu II (Aβ 4–16 ) ATCUN motif once the Cu II is anchored to the peptide [21] . Additionally, the value found for Cu II (Aβ 11–16 ) is consistent with the value very recently determined [22] for the short GGH peptide by classical stopped‐flow experiments and attributed to the reshuffling of the Cu II site forming the ATCUN motif after initial anchoring to the N‐terminal and side‐chain of His groups. In addition, it was not possible to measure the rate of Cu II binding to Aβ 1–16 under the very same conditions, thus indicating that Cu II anchoring to the peptide (mainly via His or carboxylate containing amino‐acid residues), [11c] is much faster (Figure S1).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The value found for Aβ 4–16 agrees fairly well with that recently determined by competition and double mixing stopped‐flow experiments and attributed to the formation of the Cu II (Aβ 4–16 ) ATCUN motif once the Cu II is anchored to the peptide [21] . Additionally, the value found for Cu II (Aβ 11–16 ) is consistent with the value very recently determined [22] for the short GGH peptide by classical stopped‐flow experiments and attributed to the reshuffling of the Cu II site forming the ATCUN motif after initial anchoring to the N‐terminal and side‐chain of His groups. In addition, it was not possible to measure the rate of Cu II binding to Aβ 1–16 under the very same conditions, thus indicating that Cu II anchoring to the peptide (mainly via His or carboxylate containing amino‐acid residues), [11c] is much faster (Figure S1).…”
Section: Resultssupporting
confidence: 91%
“…). However we can propose a linearly bound Cu II species in which the Cu II might be linked by two His (reminiscent from Cu I site) or by one His and the N‐terminal amine, based on recent articles aimed at deciphering the first species appearing during the formation of Cu II (Aβ 4–16 ) ATCUN [21] and Cu II (GGH) ATCUN [22] In the presence of Cu II (Aβ 1–16 ), the time required for Cu II to become bound inside the N ‐truncated peptides is at least one order of magnitude longer than for Cu II (compare Figures S1 and S8) and there is no ROS produced provided that the mixture time between Cu II (Aβ 1–16 ) and the Aβ 4/11–16 is long enough.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Indeed, the Cu II -transfer between the ATCUN (XZH) motif and a partner biomolecule (L) seems to occur via a transient ternary complex, which is a transition state where Cu 2+ is bound partially to XZH and partially to L. [26] In particular, a 2N (NH2, NIm) species has been recently identified as intermediate in the Cu II self-exchange of ATCUN complexes. [27] It can be speculated that an analogous (2N)-Cu II -L acts as an intermediate in the Cu II -transfer between XZH and L. To date, both the protonation of the amide groups and the overall rearrangement of the ligands around Cu II have been proposed as limiting step in the formation of such transition state. [27] Notably, the canonical XZH motif has to de-coordinate and protonate two amidates to form the supposed transition state ternary complex.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, trimeric organization may maintain in close vicinity several Cu(II) and Cu(I) sites in the trimers, and/or promote weak interactions between the residues, resulting in a change of the second coordination sphere and facilitating the transition. Two recent publications studied reduction reactions of Cu(II)-ATCUN motifs, 13,14 and they suggested that Cu(II) bound to the 4N in ATCUN is not reduced, but a low populated state in equilibrium, where Cu(II) is bound to only two nitrogen donors (terminal NH 2 , Im). 14 This state with non-saturated equatorial coordination by the peptide could bind external ligands (such Glu) 13 or a reducing agent.…”
mentioning
confidence: 99%